The mathematics textbook – from artefact to instrument - Johansson, Monica (NOMAD Nordic Studies in Mathematics Education, 2005)
This paper describes the mathematics textbook from two sides, the textbook as an artefact and the textbook as an instrument. It includes results from analysis of textbooks from different parts of the world as well as studies of the actual use of textbooks. It is not an attempt to give complete coverage of previous research in the area; it is rather an attempt to highlight some important issues.